Representações sociais de direitos humanos de estudantes pessoenses de escolas públicas e privadas - Feitosa, Izayana Pereira (2009)
The purpose of this study was to know the representations of children and adolescents about Human Rights. In order to do it, the Psycho-sociologic Theory of Willem Doise about the Human Rights was adopted. 400 students of public and private schools of the city of João Pessoa participated of the study. The ages varied from 8 to 12 years old (children) and from 14 to 18 years old (adolescents) and they were equally divided in terms of gender. The instruments were composed by: 1) Socio-demographic Questionnaire and 2) a semi-structured interview about the Rights. The instruments were administrated in two ways: individually for children and collectively for adolescents. Firstly, transcriptions of individual interviews were made and after this a Bardin content analysis about the open questions and non-parametric statistic analysis (Chi-square) were performed. The rights mentioned by the students are registered in juridical and institutional documents, just like the Universal Declaration of Human Rights. The students mentioned they have access to different and varied sources of information about human rights, however, in general, the school was mentioned more frequently by the participants. Firstly, children mentioned the school as a source of information about rights and, secondly, they said nobody had told them about the theme; they had learnt by themselves. On the other hand, the adolescents highlighted the media and friends as sources of this knowledge. When considered the kind of school, the public school students said they had known about the rights by friends or they didn‟t know, but the private school students said they had heard about the rights in the school. When considered the rights known by the participants of this study, it is verified that the students elaborated their answers related to a group of elements emphasized by the UDHR. The right to education was more mentioned by the students, followed by the rights to leisure, housing and feeding. The public school students mentioned the rights to well-being and to work; however the right to feeding was said by the private school students. The analysis of the question for you what does have a right‟ mean? demonstrated that only the variable age/level of school influenced the representations about the rights. In relation to why is important to respect the rights, the representations of children were objectified in To Assure rights and in To Avoid negative consequences, and in vague and without content answers, as well. The adolescents showed answers objectified as Social Harmony and Equality. In relation to the differences found in the answers of the students of different schools about the reason to respect the rights, it is verified that the representations of the students of the public school were objectified in the idea of To Avoid negative consequences and there were answers classified as Non-relevant; but the representations of the private school students were objectified in the conceptions of Legality. In terms of rights considered as respectable, children mentioned the right to respect, housing, protection, security, work, duty, and increase; the adolescents said none or few rights are respected, highlighting disrespect to the rights in our country by the adolescents. The results were discussed based on the Social Representations Theory and in pertinent empiric studies. It was inferred that the representations about human rights of the students of this study were anchored in the variables related to age/level of school and the kind of school, in the socialization experiences, corroborating the conceptions of Doise.